Penerapan Teknik Stress Inoculation Training (SIT) untuk Mereduksi Post Traumatic Stress Disorder (PTSD) pada Remaja Korban Kekerasaan Seksual (Studi Kasus Klien “R”) - Dari, Ayu Fitria Wulan; Razzaq, Abdur; Noviza, Neni (Scidacplus, 2023)
This study analyzes the Application of Stress Inoculation Training (SIT) Techniques to Reduce Post Traumatic Stress Disorder (PTSD) in Adolescent Victims of Sexual Violence (Case Study of Client